Quantitative magnetic resonance imaging and histological hoof wall assessment of 3‐year‐old Quarter Horses. (7th November 2019) - Pownder, S. L.; Caserto, B. G.; Bowker, R. M.; Lin, B.; Potter, H. G.; Koff, M. F.
Summary: Background: Few noninvasive methods are available for equine hoof wall evaluation. The highly organised wall structures and composition of proteoglycans and collagens may make this region amenable to quantitative MRI (qMRI) techniques of T1ρ and T2 mapping to identify pathology related to proteoglycan content and collagen organisation respectively. Objective: To establish normative T1ρ and T2 values of the equine hoof wall of 3‐year‐old Quarter Horses with histological comparison. Study design: Cadaveric anatomical study. Methods: Six cadaveric left thoracic feet from 3‐year‐old racing Quarter Horses with no reported lameness were evaluated using T1ρ and T2 mapping. Mapping was performed at six regions of interest at the toe of each hoof including proximal and distal regions of the inner epidermis, stratum lamellatum and corium. Histology was evaluated for standard hoof morphology and proteoglycan staining. Results: T2 values of the stratum lamellatum and corium were similar (42.9 [95% CI: 41.6–44.2] ms and 44 [95% CI: 42.7–45.3] ms respectively), but both were significantly different to the inner epidermis (35.8 [95% CI: 34.5–37.1] ms, P<0.001). T1ρ values for the inner epidermis, stratum lamellatum and corium were significantly different (25.1 [95% CI: 23.1–27.1] ms, 44.4 [95% CI: 42.4–46.4] ms and 50.1 [95% CI: 48.1–52.1] ms, respectively, P<0.001). Histology demonstrated normal organised morphology. Proteoglycan staining was only visible in the stratum lamellatum and corium. Main limitations: Cadaveric study with frozen samples used. Conclusions: Variation of qMRI metrics through the depth of the equine hoof wall was found. Although the highly ordered environment of collagen may contribute to T2 values, there was lack of evidence to support proteoglycan content as a major contributor of T1ρ values. It is possible T1ρ values had a greater dependence on total water content as the lowest values were seen in the epidermis. Additional research using qMRI is needed to determine mapping values in different disease states.